Study on the Awareness and Practice of Circular Economy Principles among Construction Stakeholders in Nigeria - Ayodeji Emmanuel Oke; Oladoyin Abidemi Akintola; Mercy Oluwatobiloba Oyewole; John Aliu; Nicholas Ipinlaye Omoyajowo (Construction Economics and Building)
The Nigerian construction industry, characterized by a linear  economic model and being a major contributor to waste generation, is slow in the adoption of methods that could be beneficial in sustainable waste disposal techniques. Despite the known benefits of circular economy principles (CEPs), the awareness level and usage of circular economy are still considered to be below average. This study aims to analyze the level of awareness and usage of CE principles among Nigerian construction stakeholders. It adopts a quantitative research method by using closed-ended questionnaires distributed to construction professionals in Lagos State, Nigeria. Data were analyzed using frequency distribution for the proportion of responses and characteristics of the respondents and mean item score, standard deviation, and factor analysis for the objectives. Additionally, the Kaiser–Meyer–Olkin (KMO) measure of sampling adequacy was used to indicate that the retrieved data were sufficient for factor analysis, while Bartlett’s test of sphericity (BTS) tested the significance of the correlations between the variables. The findings of the study indicate that construction professionals have only a basic knowledge of CEPs and their importance in practice, but they are very familiar with their application. Thus, it provides the basis for which construction stakeholders, policymakers, and the government can make informed decisions to improve the awareness and usage of CEPs in the construction industry. The study’s findings highlight the knowledge gap and the need for targeted educational and training initiatives, which can serve as a basis for future research and intervention programs.